The Influence Model of Reliability, Assurance, Tangibles, Empathy, Responsive-ness on Customer Satisfaction and Highway Users Loyalty - Waluyo , Minto; Sumiati; Waluyo, Mohammad Rachman (Nusantara Science and Technology Proceedings)
To harmonize the government program of the National Non-Cash Movement (GNNT), PT. Jasa Marga does service improvement by implementing E-Toll. The implementation of the E-toll service is deemed not fully implemented according to the expected goals. This is evident from the existence of several problems that occur such as double detach, the E-toll card is not read by the reader contactless machine, and the gate is not open, all transaction services become dissatisfied. This study aims to determine the effect of reliability, assurance, tangibles, empathy, and responsiveness variables on customer satisfaction and loyalty of toll road users at PT. Jasa Marga Surabaya - Mojokerto Indonesia. Respondents in this study were toll road users who had crossed the Surabaya - Mojokerto toll road at least once, the number of respondents was 120. This study used the Structural Equation Modeling (SEM) method which was processed using AMOS 22 software. The results showed that the Reliability variable had a significant effect on customer satisfaction, Assurance does not have a significant effect on customer satisfaction, Tangible has no significant effect on customer satisfaction, Empathy has no significant effect on customer satisfaction, Responsiveness has a significant effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty and the model equation is as follows Y2 = 0.207 X1 + 0.114 X2 + 0.04 X3 + 0.161 X4 + 0.191 X5